Characterization of surface topography and chemical composition of mini-implants - Knop, Luegya Amorim Henriques [UNESP]; Soares, Ana Prates; Shintcovsk, Ricardo Lima [UNESP]; Martins, Lidia Parsekian [UNESP]; Gandini, Luiz Gonzaga [UNESP] (FapUNIFESP (SciELO), 2015)
Aim: To assess the surface topography and chemical composition of three brands of as-received mini-implants (SIN®, Morelli®, and Conexao®). Methods: Twelve mini-implants of each brand were analyzed by scanning electron microscopy and energy dispersive X-ray (EDX). Results: There was no significant differences among SIN®, Morelli®, and Conexao® mini-implants comparing their surface topography by visualization of SEM micrographs and analysis of scores. The EDX analysis showed statistically significant difference among them for the amount of Ti, Al and V. Miniimplants SIN® presented also N and O in their composition. Conclusions: In conclusion, the miniimplants Morelli®, SIN® and Conexao® presented Ti as main component of the alloy. Remaining components, such as Al and V, were also observed in all the analyzed brands, with differences among them. Only SIN® mini-implants presented N and O. As far as surface topography is concerned, there are no differences among the three brands of mini-implants.
Keywords: Orthodontic anchorage procedures; Orthodontics; Titanium